Building Better Boyhood Programs Evaluation of Programs Funded by the African American Men and Boys Task Force Initiative - Schultz, Dana (RAND Corporation, 2015)
This report evaluates the implementation of programs funded by The Heinz Endowment's African American Men and Boys Task Force initiative in Allegheny County, Pa., and to understand how the programs operated, whether they made progress toward achieving their goals, and what can be learned from their implementation.